1994
DOI: 10.1136/gut.35.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol, and analgesics in dyspepsia and among dyspepsia subgroups: lack of an association in a community.

Abstract: Dyspepsia is common in the general population, and despite a paucity of data, smoking, alcohol, and analgesics are believed to be important risk factors. Dyspepsia was significantly more common in younger subjects and females. Adjusting for age and gender, paracetamol (odds ratio (OR)=2*2), aspirin (OR=1-8), and smoking (OR=1.5), but not alcohol (OR=0-9), were associated with dyspepsia (all p<0 05). When non-gastrointestinal somatic complaints were included in the logistic models, however, these environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 17 publications
(7 reference statements)
4
50
1
2
Order By: Relevance
“…7 Talley et al, following a questionnaire study conducted in Minnesota, have reported higher incidence of dyspepsia among younger age groups and females. 8 In our study, no significant difference was noticed in dyspeptic symptoms among different occupational groups. But Sonnenberg and Haas have reported higher incidence of gastric and duodenal ulcer and non-ulcer dyspepsia among manual labourers in German population.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…7 Talley et al, following a questionnaire study conducted in Minnesota, have reported higher incidence of dyspepsia among younger age groups and females. 8 In our study, no significant difference was noticed in dyspeptic symptoms among different occupational groups. But Sonnenberg and Haas have reported higher incidence of gastric and duodenal ulcer and non-ulcer dyspepsia among manual labourers in German population.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have shown that NSAID can provoke dyspepsia, and the incidence was less with COX-2 inhibitors. 12,13 But such a relation was not noticed by Talley et al 8 Epigastric pain and epigastric burning sensation were the main symptoms among our patients. Shah et al found abdominal fullness, abdominal pain, heartburn and belching as the most common symptoms in their study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While not consistently shown in every study [20][21][22], smoking's correlation with an increased upper gastrointestinal symptom prevalence (compared to abstainers) has been demonstrated to exist in a fair number of observational studies [8,20,[23][24][25].…”
Section: Current Smokingmentioning
confidence: 99%
“…The finding of higher prevalence rates of upper gastrointestinal symptoms in patients with cardiovascular disease may exist for a number of reasons. First, there are a host of mutual risk factors for developing both cardiovascular disease and upper gastrointestinal symptoms [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Next, patients experiencing both health problems often complain of similar or overlapping symptomatology, potentially resulting in the more frequent surveillance and diagnosis of both [38].…”
Section: Introductionmentioning
confidence: 99%